Gender and General Strain Theory: A Comparison of Strains, Mediating, and Moderating Effects Explaining Three Types of Delinquency. (May 2017) - Moon, Byongook; Morash, Merry
The present study of 659 Korean adolescents tests General Strain Theory's (GST) utility in explaining gender differences in delinquency causation. It models the effects of key strains, negative emotions, and a composite measure of several conditioning factors separately for boys and girls and for delinquency. Consistent with the theory, males and females experience different strains and different emotions in response, and they vary in influences hypothesized to alter the connections of strains or emotions to delinquency. Strains that males experience more than females are significantly related to their violent and property delinquency, and those concentrated among females explain their status offending. For boys, family conflict influences different types of delinquency and examination-related strain predicts violent and status offending. The empirical research suggested that GST falls short in explaining boys' and girls' property and status offending, and in showing how a composite measure of conditioning factors act as a moderator in explaining their delinquency.